2022
DOI: 10.3390/polym14101943
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Waste Material from Biobags: 3D Printing Process and Thermo-Mechanical Characteristics in Comparison to Virgin and Composite Matrices

Abstract: The purpose of this study is to limit the environmental impact of packaging applications by promoting the recycling of waste products and the use of sustainable materials in additive manufacturing technology. To this end, a commercial polylactide acid (PLA)-based filament derived from waste production of bio-bags is herein considered. For reference, a filament using virgin PLA and one using a wood-based biocomposite were characterized as well. Preliminary testing involved infrared spectroscopy, differential sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…One of the notable benefits of this growing technology is the reuse of discarded thermoplastic materials to produce quality products [24].…”
Section: Fused Deposition Modelling (Fdm) Technology Of Thermoplastic...mentioning
confidence: 99%
“…One of the notable benefits of this growing technology is the reuse of discarded thermoplastic materials to produce quality products [24].…”
Section: Fused Deposition Modelling (Fdm) Technology Of Thermoplastic...mentioning
confidence: 99%
“…Many authors have suggested the DRAM process as a cost-effective technique to produce highquality filaments for Fusion deposition modeling printers that use melting and extruding to create prototyping parts. However, the compatibility of DRAM with SLS is an ongoing study that has the power to revolutionize the polymer waste recycling industry [10]. Nonetheless, the compatibility of DRAM is highest with stereolithography, as the closed-loop system easily works with the process called photopolymerization.…”
Section: Literature Review a The Concept Of 3d Printingmentioning
confidence: 99%
“…In the last 30 years, additive manufacturing (AM) has evolved as a new digital technology that is versatile, flexible, and highly adjustable for creating three-dimensional items with complicated geometry and precise shape using computer-aided design (CAD) [16]. Metallic, ceramic, and polymeric materials, as well as mixtures in the form of composites and hybrid systems, can be used to produce 3D parts/objects [17][18][19]. Given the wide range of material flexibility and design freedom, efforts have been focused on producing bio-based filaments to develop sustainable 3D-printed objects and replace fossil-based conventional plastic filaments [20,21].…”
Section: Introductionmentioning
confidence: 99%